PENGGUNAAN UTANG PADA SAAT FASE PERTUMBUHAN: âKEPUTUSAN REAKTIF ATAU KEPUTUSAN RASIONAL - Raharja, Bayu Sindhu; Mranani, Muji (Optimum: Jurnal Ekonomi dan Pembangunan, 2016)
The focus of this study is to test the effect of the companyâs growth and thecompanyâs performance. This research also tests whether the poor long-termperformance of high growth company caused by the manager overreaction behaviorÂ in using debt forfi nancing decisions. Debt policy decisions serve as a form of proxyÂ decision-reactive managers in deciding the funding policy. The results of this studyÂ stated that the high growth companies have poor performance in the future. However,Â the poor performance in the future was not caused by reactive decision- makingÂ managers in using debt for fi nancing their business. This study shows the opposite, theÂ policy of the use of debt actually positively impact the companyâs performance in theÂ future. Thus, the use of debt as a source of funding when the company is in a growthÂ phase rational decisions.